Experimental Investigation on Fatigue Behavior of Wide-Flange Steel I-Beams Strengthened Using Different CFRP End Cutting Shapes - Kamruzzaman, Mohamed; Jumaat, Mohd Zamin; Ramli Sulong, Nor Hafizah; Narmashiri, Kambiz; Ghaedi, Khaled; Hosen, Md Akter (Springer Verlag, 2019)
In recent decades, the application of carbon fibre-reinforced polymer (CFRP) composites for strengthening structural elements has become an efficient option to meet the increased cyclic loads, or repair due to fatigue cracking. The premature failure due to end-debonding is a key limitation to achieve high fatigue performance of strengthened steel beams with externally bonded CFRP plates. The objective of this study is to explore the reinforcing techniques using the CFRP in-plane end cutting shapes and the triangular spew fillet of adhesive at the tips of the plate to care for fatigue damaged of wide-flange steel I-beams due to end-debonding. Four in-plane CFRP end cutting shapes were chosen, namely: rectangular, semi-elliptical, semi-circular and trapezoidal. The application of the trapezoidal end shape was found to be the best configuration for delaying the end-debonding failure mode and high fatigue life compared to the other CFRP in-plane end cutting shapes. Applying the triangular spew fillets of adhesive significantly increased the end-debonding and steel beam fracture initiation life of the strengthened beams. © 2018, Korean Society of Steel Construction.